Problems of ensuring the financial sustainability of the budgetsof the united territorial communities - Bilyk, Yuliia (My University, 2023)
Theses are devoted to the territorial communities in Ukraine that shape the development prospects based on the needs of the population. The state should perform protective and regulatory functions in this process. At present, there is a need to improve the system of functioning of the united territorial communities budgets in order to ensure the stability of budget revenues and its sustainability.
Keywords: local budget revenue; territorial communities; financial support; sustainability